Respuesta :
Answer:
1, -4, 2 + 5i, 2 - 5i
Step-by-step explanation:
First, I factor x^2 + 3x - 4
==> I get: (x - 1) (x +4)
Then, I factor (x^2 - 4x + 29)
==> And I get (2 + 5i) (2 - 5i)
You can use the quadratic formula to factor or use the "X" to solve them.
Hope this help!
Applying the factor theorem, it is found that the roots of the equation are:
[tex]x = 1, x = -4, x = 2 + 5i, x = 2 - 5i[/tex]
The factor theorem states that if [tex]x_1, x_2, ..., x_n[/tex] are roots of a polynomial, it can be written as:
[tex](x - x_1)(x - x_2)...(x - x_n)[/tex]
In this problem:
[tex](x^2 + 3x - 4)(x^2 - 4x + 29) = 0[/tex]
Thus, the roots are the values of x for which either:
[tex]x^2 + 3x - 4 = 0[/tex]
Or
[tex]x^2 - 4x + 29 = 0[/tex]
First, [tex]x^2 + 3x - 4 = 0[/tex]
Which is a quadratic equation with [tex]a = 1, b = 3, c = -4[/tex], thus:
[tex]\Delta = 3^{2} - 4(1)(-4) = 25[/tex]
[tex]x_{1} = \frac{-3 + \sqrt{25}}{2} = 1[/tex]
[tex]x_{2} = \frac{-3 - \sqrt{25}}{2} = -4[/tex]
Thus, [tex]x = 1[/tex] and [tex]x = -4[/tex] are roots.
Then, we solve [tex]x^2 - 4x + 29 = 0[/tex].
The coefficients are [tex]a = 1, b = -4, c = 29[/tex], so:
[tex]\Delta = (-4)^{2} - 4(1)(29) = -100[/tex]
[tex]x_{1} = \frac{-(-4) + \sqrt{100}}{2} = 2 + 5i[/tex]
[tex]x_{2} = \frac{-(-4) - \sqrt{100}}{2} = 2 - 5i[/tex]
Thus, [tex]x = 2 + 5i[/tex] and [tex]x = 2 - 5i[/tex] are also roots.
A similar problem is given at https://brainly.com/question/24380382